Kesantunan Berbahasa Anak Usia Dini Dalam Pendidikan Nonformal di Bagok Aceh Timur - Nabila, Putri; Azhari, Teuku; Ginting, Reza Pahlevi (FKIP Universitas Palangka Raya, 2025)
This research is aimed at describing a form of violation of early childhood politeness and explaining the form of assessment of early childhood language politeness in non -formal education in Bagok, East Aceh. This research uses a type of qualitative research. The data in this study is the speech of early childhood language interactions in non -formal education in Bagok, East Aceh. Data collection techniques in this study are observation, documentation, free consider techniques and record techniques. Data analysis techniques in this study use the theory of Miles and Huberman which include data reduction, data presentation, and drawing conclusions. Based on the results of research from all data found as many as 42 children's speech data that violated the principle of early childhood politeness at the Nurul Ilmi Recitation Center, Bagok Aceh Timur. Forms of violations of early childhood language politeness found 28 data on the maximum violation of policy, 7 maxim data receipts, 5 maxim data humility, and 2 maxim data agreement. Meanwhile, 42 data shows the form of language politeness assessment, with 28 data on the scale scale of profits and losses, 3 selected scale scale assessment data, 3 data scale assessment data, and 8 Social Scale Assessment Data.